PENGHARAMAN RIBA DALAM ISLAM - Elpianti Sahara Pakpahan (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2018)
Riba is always to be the interesting thing from classics until modern in academics or business. But now the usury still has been done in other activities, as good in buying and selling activities, account payable activities, and other transactions. In the mu’amalah (Islamic economics), the usury not only seen as an unlawful thing to do, but acts that do not have morality for users. The forbidden of usury did not happen inthe past, even though before Islam the other religion likes (Yahudi and Nasrani) forbid that practice. Besides that, the usury needs explanation concretely in that history of development in Islamic law, and the effect of usury practice. The usury in addition not accompanied by exchange compensation is prohibited by the Al-Quran. Basically the usury divided into two, the usury because of payable activities and the usury relates to buying and selling activities. The prohibition of usury in the Qur’an is given step by step. The first step describes the negative things in usury, (QS. Ar-Rum: 39). The second is about the blackness gesture of usury through the Yahudi in usury practice (QS, An-Nisa’: 160 161). The third, the Al-Qur'an explicitly forbid the usury doubled (QS: Ali Imran: 130-131). The fourth, the prohibition of riba totally in all ways (QS. Al-Baqarah: 275-280). In the Moslem, the usury is forbidden because it is not good in the aqidah side, religion,attitude, economics, and politics. The study regarding the nature of the prohibition of usury needs to be conveyed to get blessings and mercy from all forms of transactions in Islam in order to achieve Islam as Rahmatan Lil Alamin.